Depression-Related Brain Connectivity Analyzed by EEG Event-Related Phase Synchrony Measure - Li, Yuezhi; Kang, Cheng; Qu, Xingda; Zhou, Yunfei; Wang, Wuyi; Hu, Yong (Frontiers in Human Neuroscience, 2016)
This study is to examine changes of functional connectivity in patients with depressive disorder using synchronous brain activity. Event-related potentials were acquired during a visual oddball task in 14 patients with depressive disorder and 19 healthy controls. Electroencephalogram recordings were analyzed using event-related phase coherence to obtain the functional network. Alteration of the phase synchronization index (PSI) of the functional network was investigated. Patients with depression showed a decreased number of significant electrode pairs in delta phase synchronization, and an increased number of significant electrode pairs in theta, alpha, and beta phase synchronization, compared with controls. Patients with depression showed lower target-dependent PSI increment in the frontal-parietal/temporal/occipital electrode pairs in delta-phase synchronization than healthy participants. However, patients with depression showed higher target-dependent PSI increments in theta band in the prefrontal/frontal and frontal-temporal electrode pairs, higher PSI increments in alpha band in the prefrontal pairs, and higher increments of beta PSI in the central and right frontal-parietal pairs than controls. It implied that the decrease in delta PSI activity in major depression may indicate impairment of the connection between the frontal and parietal/temporal/occipital regions. The increase in theta, alpha, and beta PSI in the frontal/prefrontal sites may reflect the compensatory mechanism to maintain normal cognitive performance. These findings may provide a foundation for a new approach to assess the effectiveness of therapeutic strategies for depression.